The Relationship between Emotional intelligence, Personal effectiveness and Team spirit of Staff in Vietnamese Higher Education Institutions - Do Thi, Y Nhi; Huynh Cong, Phuong; Khuong Thi, Hue (Technium Social Sciences Journal, 2025)
This study aims to explore and analyze the relationship between emotional intelligence, teamwork spirit, and individual effectiveness of employees working in higher education institutions in Vietnam. Based on Bar-On’s (2006) theoretical model of social and emotional intelligence and group dynamics theory, the study develops a structural equation model to examine the relationships between the variables. Data were collected from 625 employees working at public and private universities through a questionnaire with validated reliability and validity. The PLS-SEM analysis results indicate that emotional intelligence has a positive and significant impact on teamwork spirit and individual effectiveness. Furthermore, teamwork spirit also plays a mediating role in the relationship between emotional intelligence and individual effectiveness. These findings highlight the importance of developing emotional competencies and building a collaborative work environment to enhance work performance in the higher education sector in Vietnam. The study proposes managerial recommendations related to emotional skills training, strengthening teamwork culture, and strategies for improving human resource effectiveness in educational organizations.